The Role of Continuous Accounting Education in Enhancing the Quality of Accounting Performance: Empirical Evidence from Accounting Departments’ Employees of University of Zakho - Gawdan, Kovan; Al-Abadi, Iman (Humanities Journal of University of Zakho, 2020)
Although the existence of international professional organizations that issue standards and rules to regulate the accounting profession, there is a weakness in the accounting performance in both theoretical and practical aspects, which led many educational institutions to work on raising the efficiency of accountants through adopting continuous educational programs that provide efficient accounting education requirements in accordance with international accounting education standards. This study aims to diagnose the role of continuous accounting education in enhancing the quality of accounting performance by analyzing main variables of the study. Four independent variables were selected naming cognitive skills, professional skills, technical skills, and ethics to be examined for showing their effect on the quality of accounting performance. To achieve study objectives and testing the hypotheses, a questionnaire was designed as a tool for collecting data in accordance with international accounting education standards and was analyzed according to statistical programs after collection of (40) valid questionnaires distributed to accountants in the University of Zakho. The study revealed that there is a significant correlation between continuous accounting education and the quality of accounting performance. It also showed a significant impact relationship between both main variables of the study amounted to (78%). This means that the study sample confirms the importance of continuous accounting education and its positive impact on performance quality. The study recommends the University Management to adopt continuous training courses in order to improve accounting employees’ skills as well as focusing on importance of profession’s ethics under a periodic control to ensure an environment that is efficient, impartial and quick in accomplishing tasks with minimal efforts.